Extending optical flare models to the UV: results from comparing of TESS and GALEX flare observations for M Dwarfs. Issue 3 (1st November 2022) - Jackman, James A G; Shkolnik, Evgenya L; Million, Chase; Fleming, Scott; Richey-Yowell, Tyler; Loyd, R O Parke
ABSTRACT: The ultraviolet (UV) emission of stellar flares may have a pivotal role in the habitability of rocky exoplanets around low-mass stars. Previous studies have used white-light observations to calibrate empirical models which describe the optical and UV flare emission. However, the accuracy of the UV predictions of models has previously not been tested. We combined TESS optical and GALEX UV observations to test the UV predictions of empirical flare models calibrated using optical flare rates of M stars. We find that the canonical 9000-K black-body model used by flare studies underestimates the GALEX near-ultraviolet (NUV) energies of field age M stars by up to a factor of 6.5 ± 0.7 and the GALEX far-ultraviolet energies of fully convective field age M stars by 30.6 ± 10.0. We calculated energy correction factors that can be used to bring the UV predictions of flare models closer in line with observations. We calculated pseudo-continuum flare temperatures that describe both the white-light and GALEX NUV emission. We measured a temperature of 10 700 K for flares from fully convective M stars after accounting for the contribution from UV line emission. We also applied our correction factors to the results of previous studies of the role of flares in abiogenesis. Our results show that M stars do not need to be as active as previously thought in order to provide the NUV flux required for prebiotic chemistry, however, we note that flares will also provide more FUV flux than previously modelled.